Strategi dan Struktur Nafkah Rumah Tangga Petani Jeruk di Kecamatan Bangli, Kabupaten Bangli, Provinsi Bali - LAKSANA, KADEK TRISNA ADI; AMBARAWATI, I GUSTI AGUNG AYU; DARMAWAN, DWI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p26, 2023)
Strategy and Income Structure of Household Orange Farmers in Bangli District, Bangli Regency, Bali Province Oranges are seasonal plants that will bear fruit when the season arrives. Citrus farmers always go through a period of waiting for harvest in this condition, they do not receive income from citrus farming. Various challenges and risks require citrus farmers to implement livelihood strategies. The implementation of a livelihood strategy utilizes the livelihood capital owned, namely: human, social, physical, financial and natural capital. This study aims to identify the livelihood capital and analyze the strategy and structure of the household income of citrus farmers in Bangli District. The selected sample is 30 respondents taken purposively, namely farmers with the criteria of having citrus plants that have been producing. Analysis of the data used is descriptive quantitative analysis by identifying livelihood capital and analyzing livelihood strategies and structures. Capital and livelihood strategies are divided into low, medium, high categories. The income structure is divided based on the area of citrus land ownership. The results showed that the livelihood capital of citrus farmers, namely social and financial capital, was high, human capital was moderate, physical capital and natural capital were low. The livelihood strategy is that the engineering of agricultural livelihoods is high, the dual income pattern and migration is low. The livelihood structure is dominated by agricultural income, namely orange farmers with medium and high land area ownership having a composition of 77% agricultural income and low land area ownership having a composition of 47% agricultural income. Based on the results of the study, it is necessary to increase human capital through non-formal education in the hope of obtaining additional income as well as increasing the strategy of double income patterns for citrus farmers with low land area holdings in the hope of becoming an alternative source of income.